2014
DOI: 10.4081/gh.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Risk map for cutaneous leishmaniasis in Ethiopia based on environmental factors as revealed by geographical information systems and statistics

Abstract: Abstract. Cutaneous leishmaniasis (CL) is a neglected tropical disease strongly associated with poverty. Treatment is problematic and no vaccine is available. Ethiopia has seen new outbreaks in areas previously not known to be endemic, often with co-infection by the human immunodeficiency virus (HIV) with rates reaching 5.6% of the cases. The present study concerns the development of a risk model based on environmental factors using geographical information systems (GIS), statistical analysis and modelling. Od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 26 publications
9
84
0
2
Order By: Relevance
“…This method has been previously used to predict spatial incidence of VL in India [33], although some other studies have used different approaches for modeling risk of leishmaniasis [34,35]. It can be observed that the high endemic areas are in northeastern part of the province in all years although there are a number of villages in the western and northern regions of the study area with high incidence of the disease during 2009–2010.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been previously used to predict spatial incidence of VL in India [33], although some other studies have used different approaches for modeling risk of leishmaniasis [34,35]. It can be observed that the high endemic areas are in northeastern part of the province in all years although there are a number of villages in the western and northern regions of the study area with high incidence of the disease during 2009–2010.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous leishmaniasis is widely distributed and usually prevalent in highland areas with occasional reports in the lowland regions of Omo (south) and Awash (central east) (Hailu et al, 2006a). The annual incidence of CL ranges from 20,000 to 50,000 cases, but this is probably an under-estimate (Alvar et al, 2012), with over 28 million people residing in regions with risk of transmission (Seid et al, 2014). The main causative agent of CL in Ethiopia is Leishmania aethiopica, however, infections due to Leishmania tropica and Leishmania major were also reported in the country (Hailu et al, 2006a,b;Abbasi et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, geographical information systems (GISs) and spatial analysis, in view of their usefulness in terms of understanding and visualizing the epidemiological behaviour of diseases such as leishmaniasis, have been important tools in achieving these objectives both in Brazil [46] and in other countries [710]. …”
Section: Introductionmentioning
confidence: 99%